Plant biology: Proteolytic release of damage signals - Morimoto, K; Van Der Hoorn, R (Elsevier, 2019)
Plants protect their wounds against pathogen invasion by releasing damage signals that induce immune responses in neighboring cells. A new study shows that a conserved bioactive peptide is released from its cytoplasmic precursor upon wounding by a metacaspase that is activated by calcium influx into the injured cell.